Megacystis-Microcolon-Intestinal Hypoperistalsis Syndrome (MMIHS): Series of 4 Cases Caused by Mutation of ACTG2 (Actin Gamma 2, Smooth Muscle) Gene - Katarzyna Ignasiak-Budzyńska; Mikołaj Danko; Janusz Książyk (Case Reports in Gastrointestinal Medicine)
MMIHS, also known as Berdon’s syndrome, is a rare disease that belongs to primary causes of CIPOS (chronic intestinal pseudoobstruction syndrome). Clinical characteristics of MMIHS are differential, but we come across the following classic symptoms: disorders of intestinal peristalsis, microcolon, and megacystis. In this article, we present a series of 4 patients with Berdon’s syndrome, in whom we managed to identify the genetic causes of MMIHS. All infants showed clinical features of bowel obstruction and dysfunction of the urinary system after birth. Two of them also manifested disorders from other systems. The prognosis for these patients is poor, but a constant betterment of management in MMIHS, in which the leading role plays TPN (total parental nutrition), causes improvement of patients’ survival.